The Theory of Restorative Justice as Legal Certainty in Economic Recovery and Balanced Justice - Tapriijiya Tapriijiya; Kurniati Kurniati; Sopi Yulesi (International Journal of Sharia and Law, 2026)
This study aims to analyze restorative justice theory as a foundation for legal certainty in restoring economic conditions and achieving balanced justice for the parties involved in a case. The use of dispute resolution mechanisms, both litigation and non-litigation, is largely determined by the concepts and objectives of dispute resolution sought by the parties, as well as the good faith of each party in resolving the case at hand. Restorative justice emerges as a response to public dissatisfaction with the current criminal justice system. This study employs a library research method, as all data sources are drawn from library materials, while the approach used is qualitative. Data sources consist of primary data in the form of relevant legislation, and secondary data comprising books and scientific journals related to the research theme. The findings indicate that restorative justice provides more tangible legal certainty compared to conventional criminal approaches, as it places the restoration of victims' economic losses as the primary priority through mediation mechanisms and compensation agreements between the parties. Furthermore, this approach has proven capable of creating balanced justice by actively involving victims, offenders, and the community in the dispute resolution process. This study concludes that the internalization of restorative justice principles within the Indonesian legal system needs to be strengthened as a more equitable and economically impactful alternative for dispute resolution.